Pest Status and Control of Termites in Rural Areas - Thakur, M. L. (Indian Forester, 1977)
Termites constitute an economically important group of insects and form an integral part of the extensive fauna of tropical countries. Of about 280 species known from the Indian Region, about 20 species are recognised as serious pests of human belongings in the rural areas. Information on the economic losses caused by these insidious insects is fragmentary to figure out and quantify the overall impact. This paper reviews the available information on the pest status of various species of termites in the rural areas and the control measures as advocated for different situations, keeping in view the apprehensions expressed by Environmentalists about the possible contamination of the surrounding environment by the excessive use of insecticides.